2020
DOI: 10.1111/1756-185x.14024
|View full text |Cite
|
Sign up to set email alerts
|

Is being barefoot, wearing shoes and physical activity associated with knee osteoarthritis pain flares? Data from a usually barefoot Sri Lankan cohort

Abstract: Aim: To identify the association between hours of being barefoot/wearing footwear, physical activity (PA) and knee osteoarthritis pain flares (KOAF). Methods: Persons with a diagnosis of knee osteoarthritis, who reported previous KOAF, were followed up in a 3 months long telephone-based case-crossover study. Exposures to risk factors were assessed every 10 days and whenever the participants experienced a KOAF. Conditional logistic regression examined associations of KOAF with following: hours of being barefoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
5
4
0
Order By: Relevance
“…The direction of our observed associations with exposure to one or more physical activities is consistent with previous study 35 , as is our positive association with knee buckling 37 . More broadly, our observed associations with a range of physical and psychosocial exposures are consistent with previous study of back pain 9 , knee/hip OA 10 , knee OA 11 , 13 and hip OA 12 , 38 . Contrasting observations on psychological associations with hip OA 39 , may be explained by different exposure measurements.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The direction of our observed associations with exposure to one or more physical activities is consistent with previous study 35 , as is our positive association with knee buckling 37 . More broadly, our observed associations with a range of physical and psychosocial exposures are consistent with previous study of back pain 9 , knee/hip OA 10 , knee OA 11 , 13 and hip OA 12 , 38 . Contrasting observations on psychological associations with hip OA 39 , may be explained by different exposure measurements.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work by Marty et al 46 showed clearly that patient-identified flares agreed well with clinician-defined flares. The similarity of findings with others 11,13,35,37 also provide some valuable replication and suggest that these associations may not be too highly sensitive to this choice of flare definition. Other signs and symptoms, for example, stiffness, swelling and functional impact may be earlier or more important initial symptoms associated with flare onset.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 72%
See 2 more Smart Citations
“…Thus, reducing the force through the knee when running could help prevent both development and progression of knee OA as well as symptom reduction during exercise [35]. The hip is another joint that is commonly affected by OA.…”
Section: The Kneementioning
confidence: 99%